The interpreter [videorecording (DVD)] - Pollack, Sydney, 1934-2008; Kidman, Nicole, 1967-; Penn, Sean, 1960-; Keener, Catherine (Universal Home Video, 2005)
In one of the hidden corridors of power at UN headquarters, translator Silvia Broome overhears a potentially explosive secret about a planned assassination attempt. But when federal agent Tobin Keller investigates her claim, is she a victim or a suspect?